IMPLEMENTASI HADIST DALAM METODE PENDIDIKAN MODERN - Maslani; Hoerotunnisa; Siti Wifa Uswatunnsolihah (AL-MUADDIB: Jurnal Kajian Ilmu Kependidikan, 2025)
This article discusses the implementation of the Hadith of the Prophet Muhammad SAW in modern educational methods through a descriptive analytical literature study approach. This research analyzes various literary sources to identify and describe the educational principles in the Hadith, as well as their relevance to modern educational methods. The research results indicate that the Hadith offers a strong value foundation for character education, learning methods, inclusive education, and the use of technology. Methods of exemplary conduct, dialogue, and student-centered approaches, as exemplified by the Prophet, are relevant to modern education. The implementation of the Hadith also emphasizes the importance of inclusive education and responsible technology use. By integrating the values of the Hadith, modern education can produce a generation that is intelligent, of noble character, and beneficial to society. This research concludes that the implementation of the Hadith in modern educational methods is a strategic step towards creating quality and character-building education.